The role of the long‐range exchange corrections in the description of electron delocalization in aromatic species. Issue 18 (24th April 2017) - Szczepanik, Dariusz W.; Solà, Miquel; Andrzejak, Marcin; Pawełek, Barbara; Dominikowska, Justyna; Kukułka, Mercedes; Dyduch, Karol; Krygowski, Tadeusz M.; Szatylowicz, Halina
Abstract : In this article, we address the role of the long‐range exchange corrections in description of the cyclic delocalization of electrons in aromatic systems at the density functional theory level. A test set of diversified monocyclic and polycyclic aromatics is used in benchmark calculations involving various exchange‐correlation functionals. A special emphasis is given to the problem of local aromaticity in acenes, which has been a subject of long‐standing debate in the literature. The presented results indicate that the noncorrected exchange‐correlation functionals significantly overestimate cyclic delocalization of electrons in heteroaromatics and aromatic systems with fused rings, which in the case of acenes leads to conflicting local aromaticity predictions from different criteria. © 2017 Wiley Periodicals, Inc. Abstract : In this article, we demonstrate that the uncorrected description of electron density delocalization approximated at the density functional theory level may lead to incompatibilities between different cyclic delocalization measures. It is illustrated that in acenes using the long‐range exchange corrected density functionals dramatically improves the performance of aromaticity indices from different criteria, which after including the long‐range exchange corrections consistently predict decreasing aromaticity going from central ring to the outermost ones.